Hydrometallurgical recovery of metals from waste printed circuit boards (WPCBs): Current status and perspectives – A review - Li, H.; Eksteen, Jacques; Oraby, Elsayed (Elsevier, 2018)
Printed circuit boards (PCBs) represent one of the most complicated and valuable components in electric and electronic equipment (EEE). Waste PCBs (WPCBs) contain more than 40 kinds of metals with a wide and variable range of concentrations, such as environmentally harmful metals (e.g. Pb, Cr, As, Cd and Hg) and others of economic value (e.g. Cu, Sn, Au, Ag and Pd). Recovery of metals from WPCBs is of great importance for both environmental protection and resource re-utilization. In contrast to metal recovery from natural resources, these secondary resources have to be essentially stripped completely of its harmful metallic content before the remaining plastic substrate can be disposed, charred or incinerated. Hydrometallurgy has been successfully used for metals recovery from primary and secondary resources around the world, owing to its easily controlled process and high recovery rates at relatively low costs, and a number of researches using various hydrometallurgical methods for metals recovery from WPCBs has been published each year since 2002. This study provides an up-to-date review of the hydrometallurgical recovery of metals from WPCBs and gives perspectives of this particular area, which is expected to provide an insight for the selection of suitable hydrometallurgical leaching and purification methods and to point out the novel and potential technologies that would be the future focuses of this area.